Improving Product Quality by Implementing ISO / TS 16949. (2015) - Pop, Liviu Dorin; Elod, Nagy
Abstract: An organization operating in the auto industry who wishes to become a first hand supplier of major automotive manufacturers in the world should plan to get certified under the standard ISO/TS 16949 because it may be a contractual requirement imposed by most of the manufacturers. The purpose of this standard is developing a quality management system that will generate continuous improvement through prevention of defects, reduction of variation and waste minimization, on the entire supply chain of the automotive industry. Among the basic means used for certification the following should be mentioned: SPC (Statistical Process Control), MSA (Measurement System Analysis), PFMEA (Potential Failure Modes and Effect Analysis), APQP (Advanced Product Quality Planning), PPAP (Production Part Approval Process). This paper describes the implementation and improvement of SPC in an ISO 9001:2008 certified organization in Romania, that planned the implementation of ISO/TS 16949 quality standard.